If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(y+1)=4y-4
We move all terms to the left:
2(y+1)-(4y-4)=0
We multiply parentheses
2y-(4y-4)+2=0
We get rid of parentheses
2y-4y+4+2=0
We add all the numbers together, and all the variables
-2y+6=0
We move all terms containing y to the left, all other terms to the right
-2y=-6
y=-6/-2
y=+3
| 262=22-w | | 3w+9-11w=23 | | 3x-222=-9x+126 | | 4.9+10m=8.37 | | 271=207-w | | 46=6x-4+3x+5 | | x^-5=3.2 | | 34=44-2b | | -120-14x=40-9x | | 4y-7+y=16+3y+1 | | 2.8+10m=8.25 | | 5=2y-9 | | 27=48-3x | | -24+8x=48+11x | | r-6.4=1.4 | | 3x+12=3(x+4)+1 | | 45+45+45+6h=304 | | 4-8-2p/6=13 | | a-(-(-4)=-3 | | 8x-120=50+13x | | 12c-12=9c+2 | | 2(4s+9)=74 | | w-9.3=3.37 | | 4=64(.5)^n | | -54-4x=-12x+66 | | 21y-8=76 | | 7(x+2)-6=5x+2(2+x) | | x-(14x-2)=36 | | 15x+10=16x-32 | | 18-2p=12-0.5p | | 110x+300=200 | | 6a-(4-a)=4a-19 |